2000
DOI: 10.1074/jbc.m910425199
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite Targets the Epidermal Growth Factor Receptor, Raf-1, and MEK Independently to Activate MAPK

Abstract: Activation of ERK-1 and -2 by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 38 publications
11
97
0
1
Order By: Relevance
“…To investigate the effect of ONOO Ϫ on ERK activation, we incubated the cultured hippocampal neurons with 0, 0.1, 0.5, or 1.0 mM SIN-1 with or without UA for 24 h. As shown in Fiugre 6 D, 1.0 mM SIN-1 significantly increased pERK level (pERK1/ ERK1: F (4,10) ϭ 14.92, p ϭ 0.001; pERK2/ERK2: F (4,10) ϭ 12.12, p ϭ 0.005), indicating ERK activation by ONOO Ϫ , which is consistent with previous reports (Zhang et al, 2000;Csibi et al, 2010). UA abolished the effect of 1.0 mM SIN-1 on ERK activation.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…To investigate the effect of ONOO Ϫ on ERK activation, we incubated the cultured hippocampal neurons with 0, 0.1, 0.5, or 1.0 mM SIN-1 with or without UA for 24 h. As shown in Fiugre 6 D, 1.0 mM SIN-1 significantly increased pERK level (pERK1/ ERK1: F (4,10) ϭ 14.92, p ϭ 0.001; pERK2/ERK2: F (4,10) ϭ 12.12, p ϭ 0.005), indicating ERK activation by ONOO Ϫ , which is consistent with previous reports (Zhang et al, 2000;Csibi et al, 2010). UA abolished the effect of 1.0 mM SIN-1 on ERK activation.…”
supporting
confidence: 81%
“…Our data show that glucocorticoids promote ERK phosphorylation via upregulating nNOS expression, and that ONOO Ϫ caused a substantial ERK activation. In fact, both NO-cGMP signaling pathway and ONOO Ϫ are implicated in ERK activation (Zhang et al, 2000;Rangaswami et al, 2009). In this study, the glucocorticoidmediated ERK activation led to hippocampal GR downregulation.…”
Section: Discussionmentioning
confidence: 66%
“…ERK activation by these environmental agents generally causes cell death (apoptosis) rather than normal cell growth and differentiation. For example, H 2 O 2 causes a cytotoxic response of mammalian connective tissue cells via the EGF receptor pathway leading to ERK activation, and a metabolic inhibitor of the ERK pathway (PD98059) blocked this cytotoxic response (23,30). We also observed that pretreatment of XTC-2 cells with PD98059 reduced the cytotoxic response of these cells to either H 2 O 2 or LPS ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid activation of ERK-2 by oxidative stress. We next evaluated whether oxidative stress would activate ERK-2 in XTC-2 cells, as has been reported in mammalian cell culture systems (23) Delayed activation of ERK-2 by LPS. We then investigated whether ERK-2 in XTC-2 cells was a target for endotoxinmediated cell stress.…”
Section: Phospho-erk/erk Ratiomentioning
confidence: 99%
“…In particular, peroxynitrite was recently shown to upregulate src tyrosine kinases (25) as well as the phosphoinositide 3-kinase Akt pathway (26). A large number of studies investigated the effects of peroxynitrite on mitogen-activated protein kinases (27)(28)(29)(30), a family of serine/threonine kinases that regulate an array of cellular activities. It was found that the three major subfamilies, extracellular signalregulated kinases, p38 mitogen-activated protein kinases, and c-Jun NH 2 -terminal kinases, are activated by peroxynitrite.…”
Section: Cell Signaling Induced By Peroxynitritementioning
confidence: 99%